Overview of the Potential Role of Malassezia in Gut Health and Disease - Spatz, Madeleine; Richard, Mathias L. (Frontiers in Cellular and Infection Microbiology, 2020)
Malassezia is the most prevalent fungus identified in the human skin microbiota; originally described at the end of the nineteenth century, this genus is composed of at least 14 species. The role of Malassezia on the skin remains controversial because this genus has been associated with both healthy skin and pathologies (dermatitis, eczema, etc.). However, with the recent development of next-generation sequencing methods, allowing the description of the fungal diversity of various microbiota, Malassezia has also been identified as a resident fungus of diverse niches such as the gut or breast milk. A potential role for Malassezia in gut inflammation and cancer has also been suggested by recent studies. The aim of this review is to describe the findings on Malassezia in these unusual niches, to investigate what is known of the adaptation of Malassezia to the gut environment and to speculate on the role of this yeast in the host physiology specifically related to the gastrointestinal tract.